PELATIHAN KOREAN FATCARONS SEBAGAI PENGETAHUAN DI BIDANG PASTRY UNTUK SISWA SISWI SMK SANTA MARIA - Febryola Indra; Shelvy Evalina; Kyani Pindy; Nga Lai Nicole Wong; Sherlly Bella Puspita; Varrell Isadora Victor (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
Community service is one of the Tridharma Perguruan Tinggi (Three Pillars of Higher Education) which aims to increase the sense of concern for the community by sharing knowledge and skills. The purpose of this community service activity is: (1) Provide training on how to make fatcarons appropriately and professionally; (2) Establish cooperation between the Faculty of Tourism, Universitas Pelita Harapan and smk Santa Maria; (3) Carrying out one of the functions of the Tridharma Perguruan Tinggi (Three Pillars of Higher Education), especially in the field of Community Service; (4) Invite SMKN Hospitality students to innovate in making fatcarons and entrepreneurship in the field of bread and cake.